An inclusive tactile based STEM activity for students with visual impairment: an electromagnet design. (26th January 2022) - Akarsu, Murat; Kizilaslan, Aydin; Simsek, Onder
Abstract: Regardless of the cost and long preparation time, tactile materials are increasingly being used in science and mathematics education for students with visual impairment. In this study, a hands-on tactile activity related to making magnets using a STEM educational approach for students with visual impairment are introduced. Supplemental data for this article is available online at https://doi.org/10.1080/00368121.2021.2025026 .